Predicting BRAF Mutations in Cutaneous Melanoma Patients Using Neural Network Analysis - Oleksandr Dudin; Ozar Mintser; Vitalii Gurianov; Nazarii Kobyliak; Dmytro Kaminskyi; Alina Matvieieva; Roman Shabalkov; Artem Mashukov; Oksana Sulaieva (Journal of Skin Cancer)
In conclusion, the developed MLP model, which relies on the assessment of 6 variables, can predict the BRAF mutation status in patients with CM, supporting decisions on patient management.